2020
DOI: 10.3390/nano10081520
|View full text |Cite
|
Sign up to set email alerts
|

Workers’ Exposure Assessment during the Production of Graphene Nanoplatelets in R&D Laboratory

Abstract: Widespread production and use of engineered nanomaterials in industrial and research settings raise concerns about their health impact in the workplace. In the last years, graphene-based nanomaterials have gained particular interest in many application fields. Among them, graphene nanoplatelets (GNPs) showed superior electrical, optical and thermal properties, low-cost and availability. Few and conflicting results have been reported about toxicity and potential effects on workers’ health, during the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Graphene oxide (GO) are carbon‐based 2D nanomaterials (NMs) with outstanding electrical, optical, and mechanical properties and are widely used in many important fields, such as environmental protection (Zhang et al, 2021), electronic devices (Kamran et al, 2019), medicine (Yildiz et al, 2021), and food packaging (Wang et al, 2022). In the working place, occupational exposure to graphene NMs has been revealed, although the exact exposure levels vary largely (Bellagamba et al, 2020; Boccuni et al, 2020; Lee et al, 2016; Ursini et al, 2021). However, it has been suggested that exposure to GO may induce adverse health effects to cardiovascular, central nervous, and immune systems, although the toxicity of GO is still in debate and thus may need further studies (Cao, 2022b; Chen et al, 2020; De Marchi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide (GO) are carbon‐based 2D nanomaterials (NMs) with outstanding electrical, optical, and mechanical properties and are widely used in many important fields, such as environmental protection (Zhang et al, 2021), electronic devices (Kamran et al, 2019), medicine (Yildiz et al, 2021), and food packaging (Wang et al, 2022). In the working place, occupational exposure to graphene NMs has been revealed, although the exact exposure levels vary largely (Bellagamba et al, 2020; Boccuni et al, 2020; Lee et al, 2016; Ursini et al, 2021). However, it has been suggested that exposure to GO may induce adverse health effects to cardiovascular, central nervous, and immune systems, although the toxicity of GO is still in debate and thus may need further studies (Cao, 2022b; Chen et al, 2020; De Marchi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The major potential routes of graphene into the body are inhalation, ingestion, and dermal adsorption 3 . Exposure to graphene is variable during its production process, involving direct interaction with the respiratory tract if adequate personal protective equipment is not used 56 . Concerns about the toxic effect of graphene on the lungs also extend to its integration into everyday products such as face masks 52 and biomedical applications such as intranasal immunization 57 .…”
Section: Discussionmentioning
confidence: 99%
“…The major potential routes of graphene into the body are inhalation, ingestion, and dermal adsorption [3]. Exposure to graphene is variable during its production process, involving direct interaction with the respiratory tract if adequate personal protective equipment is not used [54]. Concerns about the toxic effect of graphene on the lungs also extend to its integration into everyday products such as face masks [50] and biomedical applications such as intranasal immunization [55].…”
Section: Discussionmentioning
confidence: 99%